Ekstrak Daun Kersen (Muntingia calabura L.) Meningkatkan Konsentrasi GLUT 4 pada Tikus Jantan yang Diinduksi Streptozotosin-Nikotinamida - Aninditha Rachmah Ramadhiani; Mayang Tari; Galih Pratiwi; Putri Eka Janadia; Jessica Wahyu Pratiwi (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Diabetes Mellitus (DM) is a group of metabolic diseases characterised by hyperglycaemia, resulting from abnormalities in insulin secretion, insulin action, or both. Kersen (Muntingia calabura L.) leaves contain bioactive compounds, namely flavonoids, tannins, terpenoids, saponins, and polyphenols, which exhibit antioxidants and anti-diabetics. Glucose transporter (GLUT) 4 is an insulin-responsive glucose transporter in muscle and adipose tissue. This study aimed to examine the effect of Kersen leaves extract on GLUT 4 concentration in male rats induced by Streptozotocin-Nicotinamide. Diabetic rats were induced by Streptozotocin 45 mg/kg BW-Nicotinamide 110 mg/kg BW intraperitoneally, and the extract was administered orally for 14 days. Blood glucose level was measured using the Glucose Oxidase-Phenol 4-Aminoantipyrine (GOD-PAP) method, and GLUT 4 activity was assessed using the ELISA method. Statistical results showed significant differences (p<0.05) at 200, 400, and 600 mg/kg BW doses on the glucose and GLUT 4 levels. The 600 mg/kg BW group dose showed the best result with a blood glucose level of 88.22±2.31 mg/dL and a GLUT 4 level of 37.21±0.81 ng/mL. These findings demonstrate that Kersen leaves ethanol extract effectively lowers blood glucose levels and enhances GLUT 4 activity, with the most effective dose being 600 mg/kg BW.